Uncovering the relationship between project stakeholder collaboration and the digital transformation context: a mixed-method approach - Paiva, Danielle Cruz (2025)
This thesis aims to characterize and empirically describe the relationship between Project Stakeholder Collaboration and the Digital Transformation Context. It is grounded in the collaboration theory discussed in management and project research, and relevant studies on digital transformation. Supported by pragmatic epistemology, the investigation adopted a mixed-methods approach, to conduct three interconnected studies and to develop a technological product. The first study is theoretical; a systematic literature review aims to characterize the dimensions of Project Stakeholder Collaboration and the Digital Transformation Context. The initial theoretical investigation (Study 1) uncovered a conceptual five-dimensional model for Project Stakeholder Collaboration, which was adapted for project studies. Besides, it proposed a theoretical, unidimensional model for the Digital Transformation Context. As an additional theoretical contribution, this first study also clarified the duality of digital transformation in project studies: distinguishing between the digital transformation of project management processes (example: adoption of BIM) and the digital transformation that generates value through projects (example: delivering digitally enhanced products or new business models). Building on this foundation, the second study is empirical, a quantitative and exploratory investigation aims at examining the relationship between Project Stakeholder Collaboration and the Digital Transformation Context. Study 2 developed scales for both constructs, refining the theoretical model for Project Stakeholder Collaboration into three interconnected factors: Relational Norms, Focus on Shared Outcomes, and Stakeholder Engagement. This second research provided empirical evidence of a significant positive correlation with a strong effect size between the level of Project Stakeholder Collaboration and the degree of Digital Transformation Context. It also suggested that agile and hybrid project management methodologies are linked to higher levels of both collaboration and digital transformation. Deepening this understanding, the third study is also empirical, a qualitative investigation to describe how formal collaborative practices and relational norms associate to fostering Project Stakeholder Collaboration and to drive Digital Transformation Success. Study 3 described successful formal collaborative practices and relational norms, yielding descriptive models for Project Stakeholder Collaboration (encompassing collaborative culture, formal collaborative practices, and shared value creation) and Digital Transformation Success (characterized by dematerialization, collaborative digital strategy, and digital competencies). The main theoretical contribution of this third research was picturing vivid examples of the cyclical and mutually influential relationship between Project Stakeholder Collaboration and Digital Transformation Success. It demonstrated that while digital technologies provide a strategic environment for change, effective collaboration ensures the digital strategy drives technology and people toward a shared purpose and delivers measurable value. Finally, the findings of this thesis were synthesized into a technological product, the DigitalCollabInsights website, designed to guide practitioners toward leveraging their project management skills in the digital context. This practical contribution provides clear, actionable guidance on fostering effective project stakeholder collaboration, focused on shared value creation, and digital transformation success.